ACVoD: a peer-to-peer based video-on-demand scheme in broadband residential access networks. (18th June 2007) - Lin, Feng; Zheng, Changyi; Wang, Xin; Xue, Xiangyang
Providing large-scale on-demand video service is a challenging problem. Many schemes, such as batching, chaining, patching, periodic broadcast and piggybacking, could save the media server's capacity by taking the advantages of IP multicast. However, these approaches are difficult in deployment. Recent research shows that end system multicast is a feasible way to providing large-scale VoD services. In this paper, we propose a novel service model, which is called Advanced Chaining VoD (ACVoD) system, based on peer-to-peer technology in the scope of large-scale broadband residential access network. The ACVoD make use of the resources of idle users and make the video chain more stable. Simulation results show that our approach can support true VoD service well in a scalable way.